2021
DOI: 10.1111/jonm.13274
|View full text |Cite
|
Sign up to set email alerts
|

Effects of self‐rated workload and nurse staffing on work engagement among nurses: A cross‐sectional survey

Abstract: Ageing of the population and growth in the burden of noncommunicable disease, together with high turnover among registered nurses (RNs), have widened the gap between supply and demand (Marć et al., 2019;Wu et al., 2016). The shortage of RNs has seriously affected patient outcomes, especially in China. By the end of 2017, the number of RNs in China was about 3.8 million, or 2.74 RNs per 1,000 population (China Health Statistics Yearbook, 2018), which is much lower than the average of 9.2 RNs per 1,000 populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 44 publications
6
20
1
Order By: Relevance
“…Adequate staffing has been consistently cited in the literature as an important determinant of patient satisfaction, missed nursing care, adverse events and care quality (Blume et al, 2021). Moreover, a nursing work environment characterized by higher staffing levels was strongly associated with increased work satisfaction, job engagement, motivation, commitment and reduced turnover in nurses (Wang et al, 2021). In our study, higher levels of nurse staffing were associated with decreased pandemic fatigue.…”
Section: Ta B L E 3 Correlations Between Key Study Variablessupporting
confidence: 61%
“…Adequate staffing has been consistently cited in the literature as an important determinant of patient satisfaction, missed nursing care, adverse events and care quality (Blume et al, 2021). Moreover, a nursing work environment characterized by higher staffing levels was strongly associated with increased work satisfaction, job engagement, motivation, commitment and reduced turnover in nurses (Wang et al, 2021). In our study, higher levels of nurse staffing were associated with decreased pandemic fatigue.…”
Section: Ta B L E 3 Correlations Between Key Study Variablessupporting
confidence: 61%
“…For example, inculcating a correct understanding of profession, strengthening organizational support, promoting inter‐nurse relationships and timely recognition for nurses' accomplishments have all been proven to be positive strategies for improving nurses' work engagement. (Wang, Chen, et al, 2021) More importantly, the study validates the critical role of professional identity, including its effect on vigour, dedication and absorption. Nursing managers should improve the professional standards, carry out reasonable division of labour and optimize professional evaluation.…”
Section: Implications For Nursing Managementsupporting
confidence: 60%
“…In contrast to the other variables, this prediction value disappeared when nurses' work experience was added into the model as a covariate. Literature reported that individual characteristics of nursing staff (like education, skill and experience) improve performance, work engagement (Wang et al, 2021 ) and that more experienced nurses should report lower workloads (Neill, 2011 ). We supposed that work experience hinders workload perception in general and that more experienced nurses are better at dealing with the disruptions generated by multiple patient specialties.…”
Section: Discussionmentioning
confidence: 99%